Mindfulness in face recognition: Embedding mindfulness instructions in the face‐composite construction process. Issue 4 (4th May 2021) - Giannou, Kyriaki; Frowd, Charlie D.; Taylor, Jason R.; Lander, Karen
Summary: Meditative mindfulness practices, promoting sustained attention and reducing mind‐wandering, have been associated with improvements in cognitive abilities and memory. The present study explored whether a non‐meditative practice could be successfully applied in a forensic application; specifically, whether mindfulness instructions can be embedded in the face‐composite construction process to facilitate identification. Twenty participants, who were not football fans, were asked to memorise an unfamiliar footballer's face and return 24 hr later to construct a face using the self‐administered EvoFIT facial composite system. In the experimental condition, mindfulness instructions were embedded in the EvoFIT system, encouraging witnesses to focus on the target face and the process; in the control condition, participants constructed the face using the standard EvoFIT system. Naming of the composites was attempted by 24 football fans, who each viewed 10 composites, five from each condition, and then the target footballer images to ensure they were familiar with the identities. Results showed significantly higher levels of correct naming for composites constructed using EvoFIT with mindfulness instructions compared to using the standard EvoFIT. These findings indicate the potential for non‐meditative mindfulness instructions to assist face‐composite construction, improving correct naming of ensuing composites.